2021
DOI: 10.1016/j.ijid.2021.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility of asymptomatic COVID-19: Data from Japanese clusters

Abstract: Background The relative importance of asymptomatic individuals who would never develop illness, compared to those who eventually develop symptoms, has yet to be fully clarified. Methods The very first cluster data in Tokyo and Kanagawa (n = 36) were analyzed. Movement of all close contact was restricted for 14 days and they underwent laboratory testing with polymerase chain reaction. The reproduction numbers of symptomatic and asymptomatic cases were estimated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 7 publications
5
19
1
Order By: Relevance
“…Our point estimate of the relative reproduction number for asymptomatic cases (0.19) was consistent with this finding. Recently, we reported that the relative transmissibility of asymptomatic cases was 0.27 by analyzing transmission networks within an early cluster in Tokyo and Kanagawa [16]; this result was also broadly consistent with the findings of the current study. Two other contact tracing studies assessed the transmissibility of asymptomatic infections using epidemiological measurements other than the reproduction number.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our point estimate of the relative reproduction number for asymptomatic cases (0.19) was consistent with this finding. Recently, we reported that the relative transmissibility of asymptomatic cases was 0.27 by analyzing transmission networks within an early cluster in Tokyo and Kanagawa [16]; this result was also broadly consistent with the findings of the current study. Two other contact tracing studies assessed the transmissibility of asymptomatic infections using epidemiological measurements other than the reproduction number.…”
Section: Discussionsupporting
confidence: 92%
“…He et al [15] analyzed transmission data in Ningbo from January 21 to March 6, 2020 [17] and estimated the reproduction numbers of asymptomatic and symptomatic cases as 0.20 and 0.78, respectively. This finding indicated that the relative transmissibility of asymptomatic cases was below 1, and was further supported by the work of Nakajo and Nishiura in analyzing transmission trees among older adults [16].…”
supporting
confidence: 62%
See 1 more Smart Citation
“…In generation 1, the generation-based reproduction number was estimated to be 6, falling below 1 by generation 3 (Supplementary Figures 4–5; Supplementary Table 2). Inspection of probabilistic transmission networks (Supplementary Figure 6) confirmed a high value of the case reproduction number, R , for B1.1, but also supported sequential transmission of the virus within households resulting in a greater estimated value of compared to earlier studies ( Bi et al, 2020 , Endo et al, 2020 , Nakajo and Nishiura, 2021 ). A previous study by Ng et al ( Ng et al, 2020 ) involved an analysis of data from Taiwan from 2020, and found an estimated value of that was substantially larger, in part due to the small sample size in their analysis (the posterior mean of was 19.20).…”
Section: Resultssupporting
confidence: 59%
“…In a meta-analysis, Madewell et al compared the secondary attack rate around symptomatic (18%) and asymptomatic COVID-19 cases (0.7%, p < 0.001) [22]. Nowadays, questions are being raised about the real role of asymptomatic infected people in the spread of the disease [23][24][25][26][27]. Among SARS-CoV-2 positive individuals, there is a confusion between those who are asymptomatic (= no symptoms at all), which is the case for 20% of COVID-19 patients, CI 95%, 17-25 according to the review of Buitrago-Garcia et al [28], and those who are presymptomatic (= no symptoms at the time of sample collection for RT-PCR) [3,29].…”
Section: Discussionmentioning
confidence: 99%